The challenges faced by growth points in the promotion of rural development: a case study of Magunje growth point in Mashonaland west province - Bob, Shaka Keny (Midlands State University, 2017)
The intent of this research was to expose the challenges which growth points have faced in the promotion of rural development, a case study of Magunje Growth Point in Mashonaland West Province. A sample of 40 people was selected as respondents. Semi- structured questionnaires, and interviews were used to collect the information from the respondents. The research results were based on the data captured in the questionnaires and from the qualitative face to face interviews. Growth points have faced a number of challenges in the promotion of rural development. These challenges are mostly external factors which end up affecting the local economy within the growth points. Central to blame in the underdevelopment and stagnation of growth point is the central government because it is the institution which continued the inherited policy from the previous colonial regime without evaluating its effectiveness in bringing about any meaningful urbanisation to these growth points.